The impact of key monitoring policy on the usage of policy-related drugs in Hubei Province, China - Wen, Xiaotong; Wang, Yue; Chen, Xiaoze; Liu, Yuxin; Mao, Zongfu (Frontiers in Pharmacology, 2023)
Objective: This research is aimed at quantitatively evaluating the impact of the first batch of the catalog of Key Monitoring and Rational Use Drugs (KMRUD) on the Usage Patterns of policy-related drugs in Hubei Province, China. Methods: Data on the procurement records of policy-related drugs from January 2018 to June 2021 were obtained from the Drug Centralized Procurement Platform of the Public Resources Trading Center in Hubei Province. Interrupted time-series (ITS) analysis was used in this study. Results: After the implementation of the first batch of the catalog of KMRUD, the consumption of policy-related drugs decreased by 83.29% in 2020. The spending on policy-related drugs decreased by 83.93% in 2020. The introduction of the first batch of the catalog of KMRUD was associated with a significant decrease in the spending on policy-related drugs in the level (β2=-75162.92, p=0.001). After the implementation of the KMRUD policy, the long-term trend of the overall DDDs (β3=-10.40 p=0.345) and spending (β3=-1389.32 p=0.252) on policy-related drugs showed a further downward trend, but the results were not statistically significant. In the aggregated ITS analysis, the DDDc of policy-related drugs decreased significantly in the trend (change in the trend of -3.57 CNY per month; p<0.001). Conclusions: After the policy intervention, the KMRUD policy overall achieved the goal of limiting policy-related drug use and controlling cost increases. And it is recommended that the health department quantify the usage indicator of adjuvant drugs, uniform standards, and apply prescription reviews and dynamic supervision, and other measures to strengthen supervision.